2010
DOI: 10.1080/09540121003615129
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the National Pediatric Free Antiretroviral Therapy program in China

Abstract: In 2003, the Chinese Government initiated a free antiretroviral therapy (ART) program focusing on adult AIDS patients. Pediatric antiretroviral (ARV) formulations were yet unavailable. It was not until July 2005, with the initiation of a two-stage program implemented by the Chinese Ministry of Health, that pediatric formulations became accessible in China. Initially, the pediatric ART program was piloted in six provinces with the highest incidences of pediatric HIV/AIDS. The pilot stage allowed the Chinese Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…This treatment program, previously described (Zhang, Au et al, 2007;Zhang, Haberer et al, 2007, 2009Zhao et al, 2010Zhao et al, , 2011Zhao et al, , 2012, was established in July 2005 and provides free ART, free testing, and comprehensive care for HIV-infected children.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…This treatment program, previously described (Zhang, Au et al, 2007;Zhang, Haberer et al, 2007, 2009Zhao et al, 2010Zhao et al, , 2011Zhao et al, , 2012, was established in July 2005 and provides free ART, free testing, and comprehensive care for HIV-infected children.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…A study of those in the national ART programme before 2007 reported an 88% survival rate at five years of ART [45]. China's national programme had enrolled around 5100 children by 2009 [46], with 1600 on ART [23]. Although general surveillance data for children are inconsistent, Cambodia was treating 3600 and Vietnam 2000 children by 2009 [23].…”
Section: Asiamentioning
confidence: 99%
“…In this study, we focused on studying PHIVA and conducted a cross-sectional study investigating sexual health knowledge among 233 HIV-infected adolescents living in Shangcai county, Henan province of China where the first pilot of National Free Pediatric ART Program (NPATP) was initiated in 2005 (Yan Zhao et al, 2010;Zhao et al, 2013). Most children were infected with HIV perinatally in mid-1990s, and thus by 2010, *Corresponding author.…”
Section: Study Design and Participantsmentioning
confidence: 98%